2009
DOI: 10.1158/0008-5472.can-08-4631
|View full text |Cite
|
Sign up to set email alerts
|

Lack of T-Cell Receptor–Induced Signaling Is Crucial for CD95 Ligand Up-regulation and Protects Cutaneous T-Cell Lymphoma Cells from Activation-Induced Cell Death

Abstract: Restimulation of previously activated T cells via the T-cell receptor (TCR) leads to activation-induced cell death (AICD), which is, at least in part, dependent on the death receptor CD95 (APO-1, FAS) and its natural ligand (CD95L). Here, we characterize cutaneous T-cell lymphoma (CTCL) cells (CTCL tumor cell lines and primary CTCL tumor cells from CTCL patients) as AICD resistant. We show that CTCL cells have elevated levels of the CD95-inhibitory protein cFLIP. However, cFLIP is not responsible for CTCL AICD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 42 publications
(52 reference statements)
5
43
0
3
Order By: Relevance
“…42 Recently, several reports consistently demonstrated that CTCL cells, including Hut78 cells, are highly resistant to apoptosis, in particular AICD, which has been postulated to be responsible for the development and progression of CTCLs. 6,43,44 The SATB1 expression-restored Hut78 cells in our study demonstrated increased spontaneous apoptosis, compared with control Hut78 cells. When stimulated with anti-CD3 antibody or PMA/ionomycin in the presence of IL-2, which simulates the AICD process in vitro, the SATB1-restored cells showed higher rates of apoptosis.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…42 Recently, several reports consistently demonstrated that CTCL cells, including Hut78 cells, are highly resistant to apoptosis, in particular AICD, which has been postulated to be responsible for the development and progression of CTCLs. 6,43,44 The SATB1 expression-restored Hut78 cells in our study demonstrated increased spontaneous apoptosis, compared with control Hut78 cells. When stimulated with anti-CD3 antibody or PMA/ionomycin in the presence of IL-2, which simulates the AICD process in vitro, the SATB1-restored cells showed higher rates of apoptosis.…”
Section: Discussionsupporting
confidence: 47%
“…6,21 For FasL/CD95L-induced apoptosis, cells were seeded at 5 ϫ 10 5 /mL in 1 mL RPMI 1640 culture media. Super FasL (40 ng/mL; Alexis Biochemicals) was added into the cell culture and incubated for 16 hours.…”
Section: Apoptosis Assaysmentioning
confidence: 99%
See 3 more Smart Citations